Phase 1 trial of ralimetinib (LY2228820) with radiotherapy plus concomitant temozolomide in the treatment of newly diagnosed glioblastoma. (January 2021) - Biau, J.; Thivat, E.; Chautard, E.; Stefan, D.; Boone, M.; Chauffert, B.; Bourgne, C.; Richard, D.; Molnar, I.; Levesque, S.; Bellini, R.; Kwiatkowski, F.; et al.
Highlights: Phase 1 trial of concomitant ralimetinib with radiotherapy (and TMZ) in glioblastoma patients. First worldwide phase 1 trial to evaluate the combination of a p38-MAPK inhibitor (ralimetinib) with radiotherapy. The recommended dose of ralimetinib was 100 mg/12 h with chemoradiotherapy. At recommended dose, potentially ralimetinib-related toxicity included grade 3 hepatic cytolysis (13%) and rash (7%). Abstract: Background and purpose: This phase 1 trial aimed to determine the maximum tolerated dose (MTD; primary objective) of a p38-MAPK inhibitor, ralimetinib, with radiotherapy (RT) and chemotherapy (TMZ), in the treatment of newly diagnosed glioblastoma (GBM) patients. Materials and methods: The study was designed as an open-label dose-escalation study driven by a Tite-CRM design and followed by an expansion cohort. Ralimetinib was administered orally every 12 h, 7 days a week, for 2 cycles of 2 weeks at a dose of 100, 200 or 300 mg/12 h. Patients received ralimetinib added to standard concurrent RT (60 Gy in 30 fractions) with TMZ (75 mg/m 2 /day) and 6 cycles of adjuvant TMZ (150–200 mg/m 2 on days 1–5 every 28 days). Results: The MTD of ralimetinib was 100 mg/12 h with chemoradiotherapy. The three patients treated at 200 mg/12 h presented a dose-limiting toxicity: one patient had a grade 3 face edema, and two patients had a grade 3 rash and grade 3 hepatic cytolysis (66%). Of the 18 enrolled patients, 15 received the MTD of ralimetinib. At the MTD, the grade ≥ 3 adverse events during concomitant chemoradiotherapy were hepatic cytolysis (2/15 patients), dermatitis/rash (1/15), lymphopenia (1/15) and nausea/vomiting (1/15). No interaction of TMZ and ralimetinib when administrated concomitantly has been observed. Inhibition of pMAPKAP-K2 (−54%) was observed in peripheral blood mononuclear cells. Conclusion: This phase 1 trial is the first trial to study the combination of a p38-MAPK inhibitor, ralimetinib, with radiotherapy (RT) and chemotherapy (TMZ), in the treatment of newly diagnosed glioblastoma (GBM) patients. The MTD of ralimetinib was 100 mg/12 h. The most frequent dose-limiting toxicities were hepatic cytolysis and rash.